IMPLEMENTASI KEBIJAKAN OTONOMI KHUSUS PROPINSI PAPUA DALAM REKRUTMEN BRIGADIR POLISI REPUBLIK INDONESIA (POLRI) DI POLDA PAPUA - Cahyo Sukarnito; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2021)
in terms of the recruitment of the Police Brigadier at the Papua Police. Then to describe and analyze the factors that support and hinder the implementation of the Papua Special Autonomy Policy in terms of the recruitment of the Police Brigadier at the Papua Police. This study uses a qualitative descriptive research approach by relying on data from interviews with informants, observation and research documentation. The results showed that the implementation of the special autonomy policy in the recruitment of Police Brigadiers at Polda Papua which includes the content of the policy (contens of policy) and the implementation environment (context of policy), has gone well and in accordance with what was targeted. The benefits of this are very much felt, especially Papuans who can compete and be accepted as a Police Brigadier through the Papua Special Autonomy Policy. The supporting factors are internal factors that exist within the National Police itself, namely the principles of cleanness, transparency, accountability and a humanist side and the concept of Local Boy for Local Job in implementing the implementation of the Papua Special Autonomy Policy in terms of the recruitment of Police Brigadiers at the Papua Police. Meanwhile, the inhibiting factor is the lack of consistency between the implementation instructions (Julkak) and the technical guidelines (Juknis) and the implementation in the field.